THE SLCO1B1 GENE POLYMORPHISM AND STATIN-INDUCED MYOPATHY IN RUSSIAN PATIENTS - V. I. Petrov; O. N. Smuseva; Yu. V. Solovkina; O. V. Shatalova (Российский кардиологический журнал, 2014)
Aim. To evaluate the risk of muscle tissue damage in patients taking statins, and usefulness of the gene SLCO1B1 typifying for the risk estimation of such an unpleasant adverse drug reaction (ADR).Material and methods. The observation of 258 patients with ischemic heart disease, taking statins, was conducted. To evaluate the credibility of causeoutcome relation “ADR – statin” the WHO classifications and criteria were used together with Naranjo algorithm.Results. The 3 groups were stratified: I – patients with muscle pain or weakness and with probable to definite chance of the cause-outcome relation (n=31); II – patients with muscle symptoms and possible or doubtful degree of credibility for causeoutcome relation (n=27); III – patients without muscle symptoms (n=200); of those into further study we included 35 subjects. Among those with muscle symptoms women were more prevalent (I group – 61,3% (19/35); (p>0,05 in all groups). Mean time of hypolipidemic therapy of 1st group patients was 48,8 months (p<0,0001 vs 2nd and 3rd groups). Manifecting of muscle symptomatic in a majority of patients (19/35) was during the first year of therapy (RR 2,5; p=0,0841). Average doses of statins were higher in those of the 1st group: 38,3 mg/day (p I vs II=0,0004); p I vs III=0,0139). As a result of allele SLCO1B1*5 typifying a tendency of more frequent C-allele in the 1st group was found comparing to 2nd and 3rd groups: HR I vs II 2,35 (p=0,1242); RR I vs III 2,37 (p=0,0732); RR II vs III 1,00 (p>0,9999). The algorithm for statin-induced myopathy was invented.Conclusion. In patients with CHD the ADR as myopathy were found in 12% of cases. The most significant predictors: duration of hypolipidemic therapy more than12 months (RR 7,7; p=0,0002), atorvastatin usage in dose more than 40 mg per day (RR 2,67, p=0,0139). The prevalence of statin-associated muscle events was higher in women (RR 1,88, p=0,23) and carriers of allele type SLCO1B1*5 (RR 2,37; p=0,0732).